The «Andean judge» in intellectual property issues: application to the Peruvian case - Rejanovinschi Talledo, Moisés (2015)
This paper emphasizes the role of Andean Tribunal of Justice, however disagrees with criteria used to recognize administrative entities such as «national judge» or «Andean judge». If we apply the Tribunal criteria, several administrators of justice in Intellectual Property will be exempt of collaborating with Andean integration.